2021
DOI: 10.1155/2021/8812431
|View full text |Cite
|
Sign up to set email alerts
|

Strong Association of Waist Circumference (WC), Body Mass Index (BMI), Waist-to-Height Ratio (WHtR), and Waist-to-Hip Ratio (WHR) with Diabetes: A Population-Based Cross-Sectional Study in Jilin Province, China

Abstract: Backgrounds. The prevalence of diabetes has increased with the increase of obesity, and finding indicators to predict diabetes risk has become an urgent need. The purpose of this study is to compare the correlation between four anthropometric indices and the prevalence of diabetes. Methods. A total of 4052 participants aged 40 years and above were selected in Dehui City, Jilin Province, using a multistage stratified whole group sampling method. Face-to-face interviews and physical examinations were conducted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 40 publications
5
68
1
2
Order By: Relevance
“…Our study found that BMI and WC were positively associated with T2DM, and those positive associations were also found in some other studies [ 9 , 24 , 25 ]. There are several explanations for this positive association.…”
Section: Discussionsupporting
confidence: 91%
“…Our study found that BMI and WC were positively associated with T2DM, and those positive associations were also found in some other studies [ 9 , 24 , 25 ]. There are several explanations for this positive association.…”
Section: Discussionsupporting
confidence: 91%
“…Issaka et al [34] argued that WC might be the indicator most helpful in identifying those with diabetes among West African adults. However, recently, several studies introduced WHtR as a risk indicator for diabetes because it is reasonable to assume that short subjects generally have more risk factors related to abdominal fat than tall subjects with a similar WC [37][38][39][40][41][42][43]. Bell et al [28] noted that BMI was associated with a higher prevalence of hypertension in a crosssectional study of adults aged 30-65 years in China, the Philippines, and the United States.…”
Section: Plos Onementioning
confidence: 99%
“…In addition, WC is an indicator that can reflect abdominal obesity well and has been mentioned as a risk factor for diabetes [31][32][33][34] and hypertension [35,36]. However, WC does not consider height, and WHtR, which reflects the ratio of WC to height, has recently been reported as a risk factor for diabetes [37][38][39][40][41][42][43] and hypertension [30,36,44,45]. These obesity-related indicators are also known as risk factors for HDC [46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…Although the mentioned anthropometric indices have been used in various studies, their usefulness has not been systematically evaluated. Furthermore, previous studies mostly are cross-sectional designed and focus on the diabetes risk among general populations ( 17 , 18 ), lacking concern for the hypertensive patients, especially those with normal-weight central obesity.…”
Section: Introductionmentioning
confidence: 99%